2019
DOI: 10.3390/ijerph16142556
|View full text |Cite
|
Sign up to set email alerts
|

The Driving Forces of Point Source Wastewater Emission: Case Study of COD and NH4-N Discharges in Mainland China

Abstract: Excess consumption of water resources and environmental pollution have become major challenges restricting sustainable development in China. In order to prevent the pollution of water resources, policymakers should have reliable emission reduction strategies. This paper aims to contribute new knowledge by analyzing the spatial-temporal characteristics and driving forces of point source emission. The chemical oxygen demand (COD) and ammonia nitrogen (NH4-N) emission variations in 31 provinces and municipalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Since decomposition results are easy to be interpreted with the characteristics of uniqueness and consistency, the logarithmic mean divisia index (LMDI) method is widely used in the field of energy and environment [18,19,20], and gradually, its application to analyze the driving factors of water resources grew [21,22]. For instance, Li et al (2018) [23] and Chen et al (2017) [24] studied the changes of industrial water consumption and industrial wastewater discharge, respectively, and effectively identified the main influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since decomposition results are easy to be interpreted with the characteristics of uniqueness and consistency, the logarithmic mean divisia index (LMDI) method is widely used in the field of energy and environment [18,19,20], and gradually, its application to analyze the driving factors of water resources grew [21,22]. For instance, Li et al (2018) [23] and Chen et al (2017) [24] studied the changes of industrial water consumption and industrial wastewater discharge, respectively, and effectively identified the main influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…To further demonstrate the significant results of the investment in WWT in NWC, we analyzed the discharge of the two main pollution indicators for river waters in China [67,68]: the chemical oxygen demand (COD) and the ammonia nitrogen (NH 4 ), from 2003 to 2020. Although these two measurements alone do not serve as a comprehensive evaluation of the efficiency of policies established for water quality improvement, they can provide the broader picture of the evolution of water quality status since they have been traditionally the major threats for river waters [67,68]. Figure 8 shows that the major pollution discharge from wastewater in NWC presents a trend similar to an Environmental Kuznets Curve [69].…”
Section: Controlling Main Pollutants and Increasing Wastewater Treatm...mentioning
confidence: 99%
“…The previous research methods provided rich perspectives and assessments for the discussion of this relationship. However, coordination of the industrial-ecological economy is dynamic change and evolution which depends on the interaction and development level between the industrial economy and industrial ecology (Zhang et al, 2019;Xu et al, 2021). On one hand, the development of the industrial economy will drive industrial technological innovation and improve the level of industrial ecology, however, it will also lead to the consumption of resources and the discharge of pollutants, which at the same time hinders the development of the industrial economy.…”
Section: Introductionmentioning
confidence: 99%